Chemical Solutions of Fire Protection Problems - Vakhitova, L.M.; Calafat, K.V.; Drizhd, V.L.; Taran, N.А. (Science and Innovation, 2024)
The modern approaches to the creation of fire protective coatings through modifying intumescent systems by nanomaterials have been considered; chemical reaction mechanisms at high temperature have been studied. Interactions among the components of polyphosphate type intumescent blend have been researched, the correlations between the directions of chemical processes and fire retardant properties of intumescent coatings have been found. Efficient methods for raising fire-protective efficiency and improving performance characteristics of intumescent coatings (operation life, resistance to environmental factors and bio-contamination) have been proposed. The results of fundamental research have enabled developing new flame retardant compositions whose properties are confirmed by tests in accordance with existing standardized methods; these results have been commercialized.